2009
DOI: 10.1093/icesjms/fsp215
|View full text |Cite
|
Sign up to set email alerts
|

Growth of European hake (Merluccius merluccius) in the Gulf of Lions based on conventional tagging

Abstract: Mellon-Duval, C., de Pontual, H., Métral, L., and Quemener, L. 2010. Growth of European hake (Merluccius merluccius) in the Gulf of Lions based on conventional tagging. – ICES Journal of Marine Science, 67: 62–70. Growth of European hake was estimated from the results of a conventional tagging study in the Gulf of Lions, the first tagging experiment to have been undertaken on the species in Mediterranean waters. In all, 4277 hake 15–40 cm long were tagged and released on the inshore fishing grounds during spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 28 publications
4
61
1
Order By: Relevance
“…This could be due to the differences in the different growth rates of the two sexes. Indeed, a recent study of the growth of European hake using tagging and recapture techniques (Mellon-Duval et al, 2010) shows that from the second year of life, females grow faster than males.…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the differences in the different growth rates of the two sexes. Indeed, a recent study of the growth of European hake using tagging and recapture techniques (Mellon-Duval et al, 2010) shows that from the second year of life, females grow faster than males.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the diagnostic alignment of the D 14 C values measured in the otolith cores of the two largest fish, it can be concluded that the FGH underestimates maximum age and is not a valid growth scenario for the entire lifespan of European hake (Tables 1, 2). Furthermore, it must be considered that Mellon-Duval et al (2010) have validated by tag-recapture a high growth rate for 96 juvenile European hake females (,24-cm total length). At this time, the validated longevity of large adult European hake obtained in the present study and the tag-recapture validated early growth represent the only reliable length-at-age information for the Mediterranean.…”
Section: Resultsmentioning
confidence: 99%
“…Ragonese et al 2012), two opposing hypotheses are under consideration in the present study: (1) a fast-growing hypothesis (FGH), with a maximum age near 15 years (e.g. García-Rodríguez and Esteban 2002;Mellon-Duval et al 2010); and (2) a slow-growing hypothesis (SGH), with a maximum age near 30 years (e.g. Aldebert and Carries 1989;Levi et al 1994).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations